Effects and Conduct of Macroprudential Policy in China - Kim, Soyoung; Shim, Seri; Chen, Hongyi (Journal of Financial Stability, 2023)
This paper investigates the effects and conduct of macroprudential policies in China compared to those of monetary policy. Two types of structural VAR models, one with recursive zero restrictions and the other with sign restrictions on impulse responses, are used with monthly data. The main results of this paper are as follows. First, macroprudential policy has substantial effects on financial variables such as credit and house prices and macro variables such as output and inflation rate, as monetary policy does. Second, contractionary macroprudential policy is taken to stabilize credit in response to credit shocks, but monetary policy is not.